2020
DOI: 10.1108/heswbl-12-2018-0140
|View full text |Cite
|
Sign up to set email alerts
|

Improving graduate outcomes

Abstract: PurposeThis study explores how the implementation of problem-based learning (PBL) in technical and vocational education training (TVET) systems of Nigerian higher education (HE) can enhance quality graduate outcomes. The study also explores the issues and challenges of PBL implementation in the TVET system of Nigerian HE.Design/methodology/approachThis study follows the assumptions of qualitative research. The authors interviewed 55 participants and had a focus group with 7 TVET postgraduate students. The 55 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…But it is obvious that more needs to be done in this regard -this is because most students concentrate on scaling through the examinations after the classes than on getting the skills required to make them stand out after graduation. The staff members must find means of engaging the students in more meaningful activities using inquiry and problem-based approaches rather than any form of teacher-centered learning technique [10].…”
Section: Discussionmentioning
confidence: 99%
“…But it is obvious that more needs to be done in this regard -this is because most students concentrate on scaling through the examinations after the classes than on getting the skills required to make them stand out after graduation. The staff members must find means of engaging the students in more meaningful activities using inquiry and problem-based approaches rather than any form of teacher-centered learning technique [10].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study align with the sociocultural career theory in which this study is anchored and support those of previous research that showed that engaging in experiential/practice-based activities such as work-based learning, apprenticeship and internship programs has a strong positive probability on young people employability as it enhances their entrepreneurial self-efficacy and provides them with clear career direction (Kamaliah et al, 2018; Jackson, 2015). These experiential experiences, if integrated into the TVET curriculum, could stimulate learners' self-efficacy, particularly their perceptions, attitude and confidence, in tandem with the critical components of SCCT and consequently foster their capabilities of applying the knowledge and skills gained during the training in the world of work (Chen et al, 1998; Kamaruddin & Rasdi, 2021; Okolie et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Integrating work-based programs in the TVET curricula would allow the development of timely intervention mechanisms, thus combating young people’s lack of preparedness to enter into labour and their incapacity to retain employment. Adoption of WBL has been associated with improved youth employability as TVET institutions can establish partnerships with the industry, thus allowing them to understand the labour market needs (Okolie et al, 2020; Singh & Tolessa, 2019). The initiative could significantly improve students’ experiences and allow institutions to make the curriculum more relevant to the world of work.…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
“…Many of the assessed standards to train Item no Educational content 1 Community-oriented primary care (COPC): the health needs assessment and the design of population-level interventions, disease prevention, promoting the community health, cross-sectoral cooperation and coordination, leadership skills in a multidisciplinary environment and team skills especially working with specialists in other disciplines (Longlett et al, 2001;Morikawa, 2020) 2 Risk assessments and risk reductions in the individual, family and community (Entezari et al, 2017) 3 Patient management and treatment (Green et al, 2007;Flinkenfl€ ogel et al, 2014) 4 Visit in the community (home, schools, etc.) (Rieselbach et al, 2013;Entezari et al, 2017) 5 Mental health (Oakley et al, 2005;Green et al, 2007;Rieselbach et al, 2013) 6 Primary health cares in the elderly (Rieselbach et al, 2013;Green et al, 2007) 7 Primary health cares for mothers (Entezari et al, 2017;Green et al, 2007;Morris et al, 2008) 8 Primary health cares in children (Rieselbach et al, 2013;Entezari et al, 2017;Morris et al, 2008) 9 Primary health cares in adolescents, youth and middle-aged adults (Entezari et al, 2017;Green et al, 2007) 10 Health system management (Entezari et al, 2017) 11 Communication, thinking and interpersonal skills (Okolie et al, 2020;Green et al, 2007;Maizes et al, 2006;Mbuka et al, 2016) 12 The rational referral of patients to do paraclinical tests (Entezari et al, 2017;Rieselbach et al, 2013) 13 The reasonable drug administration (Entezari et al, 2017;Rieselbach et al, 2013) 14 Appropriate referral and follow-up of patients (Shariati et al, 2018;Green et a...…”
Section: Discussionmentioning
confidence: 99%